Spin‐Transport through Van der Waals Heterojunctions Based on 2D‐Ferromagnet and Transition Metal Dichalcogenides: A Study from First‐Principles Calculations. Issue 8 (2nd June 2022) - Devaraj, Nayana; Tarafder, Kartick
Abstract: Recently reported 2D ferromagnets show tremendous potential for their application in low‐dimensional spintronic devices. Semiconductor heterostructure consisting of 2D ferromagnet integrated with other suitable 2D semiconducting materials may pave the way for designing robust and sophisticated spin‐transport devices within a few nanometer scales. In this regard, a detailed understanding of the interface properties of 2D ferromagnetic materials and other 2D semiconductors is highly essential. Herein, the interface properties in the heterostructure made‐up of CrX3 (X = Cl, Br, and I) monolayer and transition‐metal dichalcogenides (TMDC; MoS2, MoSe2, and WS2 ) monolayer, using first‐principle calculations are systematically studied. This study predicts that a robust spin‐dependent barrier originated at the CrX3 /TMDC interface. It can lead to a significantly large spin‐filtering at the interface while spin‐transport through this heterojunction, which will be highly beneficial for spintronic devices applications. Further, detailed spin‐dependent transport studies carried out through Co/CrI3 /TMDC/CrI3 /Co magnetic heterojunctions and substantial tunnel magnetoresistance up to 590%, estimated for these systems. Abstract : The electronic structures and magnetic properties of a class of 2D‐ferromagnets, namely chromium tri‐halides (CrX3 ), are thoroughly investigated from the first‐principle electronic structure calculations. Spin injection and spin transport through CrI3 /Transition‐metal‐dichalcogenides/CrI3 Van der‐Waals heterostructure junctions are carefully examined. The result predicts a large tunnel‐magnetoresistance in these heterojunctions, suitable for high‐end spintronic device applications.